PENGARUH PEMBELAJARAN PREDICT OBSERVE EXPLAIN PADA MATERI PERISTIWA ALAM TERHADAP LITERASI SAINS SISWA KELAS V - Zen, Zaenudin Maulana; Subarjah, Herman; Sujana, Atep (Jurnal Pena Ilmiah, 2019)
Science Literacy is important for students to understand natural phenomena in the environment. However, science literacy of elementary students is still low. This study aims to determine the effect of learning predict observe explain (POE) on students' scientific literacy on natural event material. The design of this study was quasi-experimental using non-equivalent control group design. The population in this study were all fifth grade elementary school students in Rancaekek Subdistrict. The sample technique used was purposive sampling and obtained samples namely class V-A as the experimental class and class V-B as the control class at SDN Kencana Indah I. The instruments used were test and non-test instruments. Based on the results of the study it was found that POE learning had a positive effect on students' scientific literacy, POE learning (Gain = 0.48) was better than conventional learning (Gain = 0.18) in improving literacy skills.